Periplasmic expression of SpyTagged antibody fragments enables rapid modular antibody assembly. Issue 6 (17th June 2021) - Hentrich, Christian; Kellmann, Sarah-Jane; Putyrski, Mateusz; Cavada, Manuel; Hanuschka, Hanh; Knappik, Achim; Ylera, Francisco
Summary: Antibodies are essential tools in research and diagnostics. Although antibody fragments typically obtained from in vitro selection can be rapidly produced in bacteria, the generation of full-length antibodies or the modification of antibodies with probes is time and labor intensive. Protein ligation such as SpyTag technology could covalently attach domains and labels to antibody fragments equipped with a SpyTag. However, we found that the established periplasmic expression of antibody fragments in E. coli led to quantitative cleavage of the SpyTag by the proteases Tsp and OmpT. Here we report successful periplasmic expression of SpyTagged Fab fragments and demonstrate the coupling to separately prepared SpyCatcher modules. We used this modular toolbox of SpyCatcher proteins to generate reagents for a variety of immunoassays and measured their performance in comparison with traditional reagents. Furthermore, we demonstrate surface immobilization, high-throughput screening of antibody libraries, and rapid prototyping of antibodies based on modular antibody assembly. Graphical abstract: Highlights: Modular antibody assembly by SpyTag protein ligation using prebuilt modules Change valency, isotype, species, and site-specific labeling of antibodies in minutes Demonstration of antibody performance in various assays, including new applications Methods to prevent proteolytic cleavage of SpyTag in bacterial periplasmic expression Abstract : Hentrich et al. report that, after knockout of periplasmic proteases, antibodies with a SpyTag can be produced in E. coli with high efficiency. These antibodies can be assembled with prefabricated SpyCatcher modules into a variety of formats, reducing the time and effort for antibody format conversion or labeling dramatically.